Study of sex ratio and fecundity of fresh water mouth brooding fish Oreochromis mossambicus (Peters) - Dr. D. SATHEESH,; DR. R.S. KULKARNI, (The Bioscan, 2024)
The mouth breeding fish Oreochromis mossambicus is belongs to family, Cichilidae introduced in Indian water in 1952. Oreochromis mossambicus is found to be omnivorous and prolific breeder. It is extremely used as a food. For the study of its reproductive characters the fish is collected from the Daroji water tank with the help of local fisher man. The study is carried out for determination of sex ratio, fecundity. The male and female sex ratio was found 1:1.03 to 1: 2.7, the number of females is more than males were observed during the study period except February and November months of 2017. The average fecundity range found between 356 to 1350 during study period. The studies show that females dominate males throughout the study period and shows linear relationship between fecundity with ovary weight and body Weight.